Cosmic Ray Neutron Sensing for Simultaneous Soil Water Content and Biomass Quantification in Drought Conditions. Issue 10 (5th October 2018) - Jakobi, J.; Huisman, J. A.; Vereecken, H.; Diekkrüger, B.; Bogena, H. R.
Abstract: Understanding the feedback mechanisms between soil water content (SWC) and biomass production is important for sustainable resources management. Here we present a new method enabling simultaneous noninvasive measurements of SWC and biomass dynamics based on cosmic ray neutron sensing (CRNS). Recently, it was suggested that the neutron ratio ( N r ) between thermal neutron ( TN ) and fast neutron ( FN ) intensity contains information on other hydrogen pools like vegetation, canopy interception, and snow. The aim of this study is to evaluate the accuracy of simultaneous measurements of SWC and biomass dynamics during agricultural drought conditions using CRNS probes. To this end, we instrumented an arable field cropped with sugar beet with CRNS probes and a wireless in situ SWC sensor network. Belowground and aboveground biomass were sampled in monthly intervals. We found a linear relationship between N r and the aboveground biomass that allowed to continuously quantify the dry aboveground biomass development throughout the growing season with a root‐mean‐square error from 0.14 to 0.22 kg/m 2 . This information was used together with measured belowground biomass to correct for the effect of biomass on SWC determination with CRNS probes, which increased the accuracy of the SWC estimates considerably as indicated by the decrease of the root‐mean‐square error from 0.046 to 0.013 cm 3 /cm 3 . We anticipate that future research on the N r can further improve the accuracy of SWC and biomass estimates and extend the application of CRNS to include canopy interception, ponding water, and snow water equivalent estimation for both stationary and roving CRNS systems. Key Points: Soil water content and aboveground biomass were simultaneously and noninvasively measured using cosmic ray neutron sensing Cosmic ray neutron‐based soil water content measurements were corrected for aboveground biomass using the thermal‐to‐fast neutron ratio Noninvasive biomass observations revealed the negative effects of drought conditions on sugar beet biomass development